RESIDUAL EFFECTS OF SODIUM CHLORIDE (Common Salt) FERTILIZERS ON YIELD AND LEAF NUTRIENTS, OF COCONUTS, GROWN ON AN INLAND SOIL OF DAVAO (Mindanao, Philippines) - S.S. MAGAT; J.A. HABANA; L.M. ALFORJA (International Coconut Community Journal, 1992)
The beneficial residual effects of the previous regular applications of sodium chloride fertilizers on mature coconuts were evaluated in a long‑term experiment conducted in an inland Tugbok soil (typic Tropudalfs) of Davao, Mindanao (Philippilines). Sodium chloride (common salt) at increpasing rates of 0.0, 0.88, 1.76, 3.52. and 7.04 kg/tree per tree was tested., At higher rates of NaCl fertilizer (1.76‑7.04 kg/tree per year) applied regularly for 5 years, the residual respofise in terms of nuts and copra yield tended to, occur for a longer period of 5 years. Except soil Na, soil. properties were not significantly affected by NaCl application. Implications of the findings are discussed in relation to sound coconut crop agronomy and soil management.